2014
DOI: 10.1111/jen.12121
|View full text |Cite
|
Sign up to set email alerts
|

Field response of non‐target beetles to Ips sexdentatus aggregation pheromone and pine volatiles

Abstract: Although mass trapping cannot be a definitive control measure, it is one of the few ones available to contain the destruction of millions of cubic metres of conifer forests perpetrated every year worldwide by bark beetles. However, using bark beetle aggregation pheromones during both monitoring and control programs may negatively affect other saproxylic insects. The aim of this study was to describe the response of both Ips sexdentatus and its saproxylic beetle associates, especially predators, to traps baited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 65 publications
3
24
2
1
Order By: Relevance
“…; Panzavolta et al. ). Thus, any advantage of incorporating this terpene into an attractant blend would be outweighed by the detrimental effects of the removal of non‐target organisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Panzavolta et al. ). Thus, any advantage of incorporating this terpene into an attractant blend would be outweighed by the detrimental effects of the removal of non‐target organisms.…”
Section: Discussionmentioning
confidence: 99%
“…4d), with null effect. This non-specific monoterpene was found to be attractive to a wide range of non-target cortical beetles and their natural enemies (Schroeder and Weslien 1994;Erbilgin and Raffa 2000;Etxebeste et al 2012;Hofstetter et al 2012;Miller et al 2013;Macias-Samano et al 2014), such as Thanasimus formicarius (Coleoptera: Cleridae) that is commonly found in areas occupied by M. sutor (Schroeder 2003;Pajares et al 2004;Gallego et al 2008;Panzavolta et al 2014). Thus, any advantage of incorporating this terpene into an attractant blend would be outweighed by the detrimental effects of the removal of non-target organisms.…”
Section: Attraction To Pheromone-kairomone Blendsmentioning
confidence: 99%
“…It has long been known that pheromone-baited traps attract more than the intended targets, and a concerted effort has been made to increase trap and pheromone specificity and decrease capture of non-target insects (e.g., Fleischer et al 2005;Martín et al 2013;Meagher and Mitchell 1999;Mori and Evenden 2013;Panzavolta et al 2014). Yet, there is still much to be learned about which trap features can be modified to minimize bycatch of beneficial insects.…”
Section: Discussionmentioning
confidence: 99%
“…Some predators have also evolved to detect these pheromones and may use them to identify and locate prey (Zhu et al 1999, Verheggen et al 2007. Although there have been many efforts to increase trap and pheromone specificity and decrease capture of non-target insects (e.g., Fleischer et al 2005, Martín et al 2013, Mori and Evenden 2013, Panzavolta et al 2014, some trap and lure combinations are so attractive to beneficial insects that they become unacceptable pest management tools (Aurelian et al 2015). In general, knowledge of pheromone lure effects on non-target insects is lacking for most species-specific blends, particularly those used during nationwide invasive pest surveys supported by the Cooperative Agricultural Pest Survey (CAPS) program (http://caps.ceris.purdue.edu) (Spears and Ramirez 2015).…”
mentioning
confidence: 99%
“…Nevertheless, semiochemicals released from traps are also used as kairomones by competitor species, like woodboring beetles in the genus Monochamus Dejan (Allison et al, 2001(Allison et al, , 2004 or by predators, mainly clerid, histerid and nitidulid beetles (Bakke and Kvamme, 1981;Hansen, 1983;Avtzis, 1991). The number of non-target species captured is even higher when host volatiles are associated to pheromone baits (Miller et al, 2011;Panzavolta et al, 2014), because host volatiles are used by many species as kairomones to find their oviposition substrate or their prey. Consequently, knowing which non-target species respond to different pheromone lures or combinations of pheromone and host volatiles may be relevant to understand the chemical ecology of different insect species, to study the abundance of the bark beetle predators (Williams et al, 2009;Sharon et al, 2012), to selectively remove pests (Aukema et al, 2000;Dahlsten et al, 2003), or to simultaneously attract a variety of target pest species (Hanks et al, 2012).…”
Section: Introductionmentioning
confidence: 99%